2013
DOI: 10.1017/s1352465813000325
|View full text |Cite
|
Sign up to set email alerts
|

Positive Beliefs about Rumination Are Associated with Ruminative Thinking and Affect in Daily Life: Evidence for a Metacognitive View on Depression

Abstract: Our results add ecologically valid corroborating evidence for the metacognitive model of emotional disorders within the framework of self-regulatory executive function theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
(33 reference statements)
0
11
1
Order By: Relevance
“…The theory proposes that rumination impedes the effective problem-solving process partly because it makes the thinking process more pessimistic and fatalistic. Despite this, people who are ruminating believe that persistently thinking about an instrumental theme is beneficial for themselves (Kubiak et al, 2014).…”
Section: Rumination Brooding and Reflectionmentioning
confidence: 99%
“…The theory proposes that rumination impedes the effective problem-solving process partly because it makes the thinking process more pessimistic and fatalistic. Despite this, people who are ruminating believe that persistently thinking about an instrumental theme is beneficial for themselves (Kubiak et al, 2014).…”
Section: Rumination Brooding and Reflectionmentioning
confidence: 99%
“…Weber and Exner (2013) (Beck et al, 1996), RRS-SF Ruminative Responses Scale, Short Form (Treynor et al, 2003), IDS-SR Inventory of Depressive Symptomatology, Self-Report (Rush et al, 1996), LARSS The path analysis testing the metacognitive model showed that NBRS uncontrollability was not associated with depressive symptoms significantly more variance in time 2 rumination after controlling time 1 rumination. Kubiak et al (2014) carried out an ecological momentary assessment (EMA) and examined the effect of the PBRS on rumination and positive affect. They found that the PBRS predicted rumination and that the effect of the PBRS on momentary positive affect was significantly mediated by rumination, while the direct effect was not significant.…”
Section: Nonclinical Samplementioning
confidence: 99%
“…Only one study (Kraft et al, 2019) used a longitudinal design with a five-time interval over 12 months. The latent growth model showed that the PBRS, the NBRS, and rumination predicted depression levels.…”
Section: Clinical Samplementioning
confidence: 99%
See 1 more Smart Citation
“…According to the Self-Regulation Executive Function (S-REF) model [5], rumination-directing attention toward monitoring for self-related negative feelings and thoughts is activated and guided by metacognitive beliefs that exist in the form of knowledge, experiences, and strategies [6]. The occurrence of negative experiences activates positive metacognitive beliefs about the usefulness of rumination (threat monitoring), while negative metacognitive beliefs about the uncontrollability of thoughts and the terrible consequences lead to the follow-up activation of perseverative thinking [7]. Previously depressed patients have reported higher metacognitive awareness than currently depressed individuals to avoid depressive episodes, which are regarded as traumatic life events, in the future [8].…”
Section: Introductionmentioning
confidence: 99%